2020
DOI: 10.1371/journal.pone.0236402
|View full text |Cite
|
Sign up to set email alerts
|

The role of histology on endometrial cancer survival disparities in diverse Florida

Abstract: Background Endometrial cancer (EC) mortality is particularly high among non-Hispanic Blacks and is twice that of non-Hispanic Whites. However, comparisons of EC survival outcomes by race/ ethnicity are often confounded by histology and grade. Here, we analyze EC survival disparities in multiracial Florida with a focus on EC types (1 and 2) and subtypes, defined according to histology and grade. Methods All 27,809 cases of EC diagnosed during 2005-2016 were obtained from the Florida Cancer Registry. Age-standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 51 publications
1
33
0
Order By: Relevance
“…In general, they are less well differentiated and have worse prognoses than Type I tumors, and they are responsible for a disproportionate number of endometrial cancer deaths. The increased incidence of Type II compared with Type I tumors is consistent with the worse 5-year disease-specific survival of Black (51–57%), compared with White (65–67%), Hispanic (64–69%) and Asian (67–72%) endometrial cancer patients in a California registry study ( p < 0.0001) [ 12 , 21 ]. In a Florida registry study, Black endometrial cancer patients had a higher incidence of Type II tumors (57.6%) compared with White (35.6%), Hispanic (37.7%) and Asian (43.0%) endometrial cancer patients, and a 24% high risk of death due to endometrial cancer compared with white patients [ 21 ].…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…In general, they are less well differentiated and have worse prognoses than Type I tumors, and they are responsible for a disproportionate number of endometrial cancer deaths. The increased incidence of Type II compared with Type I tumors is consistent with the worse 5-year disease-specific survival of Black (51–57%), compared with White (65–67%), Hispanic (64–69%) and Asian (67–72%) endometrial cancer patients in a California registry study ( p < 0.0001) [ 12 , 21 ]. In a Florida registry study, Black endometrial cancer patients had a higher incidence of Type II tumors (57.6%) compared with White (35.6%), Hispanic (37.7%) and Asian (43.0%) endometrial cancer patients, and a 24% high risk of death due to endometrial cancer compared with white patients [ 21 ].…”
Section: Resultsmentioning
confidence: 67%
“…The increased incidence of Type II compared with Type I tumors is consistent with the worse 5-year disease-specific survival of Black (51–57%), compared with White (65–67%), Hispanic (64–69%) and Asian (67–72%) endometrial cancer patients in a California registry study ( p < 0.0001) [ 12 , 21 ]. In a Florida registry study, Black endometrial cancer patients had a higher incidence of Type II tumors (57.6%) compared with White (35.6%), Hispanic (37.7%) and Asian (43.0%) endometrial cancer patients, and a 24% high risk of death due to endometrial cancer compared with white patients [ 21 ]. A national population-based study of 35,850 young women (<50 years of age) with endometrial cancer found that the young Black patients (3903) had higher mortality compared with the young White patients [ 19 ].…”
Section: Resultsmentioning
confidence: 67%
“…It was observed that 69.4% of the women's population were White women, out of which 64.4% were diagnosed with grade I type of uterine cancer. The grade II type of uterine cancer was exhibited at a higher proportion by 57.6% of Black women, followed by 43.0% in Asian women, 37.7% in Hispanic women, and 35.5% in white women 80 .…”
Section: L-191mentioning
confidence: 89%
“…Moreover, cancer of the uterine body is the thirteenth deadliest cancer in the female population worldwide, with a mortality rate that is twice as high in regions of the world with a high or very high HDI compared with that in regions with a low or medium HDI [ 1 ]. The prognosis of endometrial cancer depends on the stage, histology, grade and ethnicity of the woman [ 2 ]. In fact, endometrial cancer mortality appears to be much higher in Black women than in Caucasian, Hispanic and Asian women, also because the former are significantly more frequently affected by endometrial cancer with a histology other than low-grade endometrioid, which is most often diagnosed at an early stage [ 2 ].…”
mentioning
confidence: 99%
“…The prognosis of endometrial cancer depends on the stage, histology, grade and ethnicity of the woman [ 2 ]. In fact, endometrial cancer mortality appears to be much higher in Black women than in Caucasian, Hispanic and Asian women, also because the former are significantly more frequently affected by endometrial cancer with a histology other than low-grade endometrioid, which is most often diagnosed at an early stage [ 2 ].…”
mentioning
confidence: 99%